Memory Training Program Decreases the Circulating Level of Cortisol and Pro-inflammatory Cytokines in Healthy Older Adults - Pesce, Mirko; Tatangelo, Raffaella; La Fratta, Irene; Rizzuto, Alessia; Campagna, Giovanna; Turli, Cinzia; Ferrone, Alessio; Franceschelli, Sara; Speranza, Lorenza; Verrocchio, Maria C.; De Lutiis, Maria A.; Felaco, Mario; et al. (Frontiers in Molecular Neuroscience, 2017)
Aging cognitive decline has been associated to impairment of the Hypothalamus Pituitary Adrenals (HPA) axis activity and a higher level of the systemic inflammation. However, little is known about the molecules driving this process at peripheral level. In addition, the cognitive function is to some extent modifiable with Memory Training (MT) programs, even among older adults and beyond. The study aims to evaluate whether MT could contribute to ameliorate cognitive performance and modulate the HPA axis activity as well the low level inflammation in the aging phenotype. Whether the phosphatase WIP-1, a negative regulator for inflammation, is involved in this process was also investigated. We recruited 31 young adults (19-28, years of age) and 62 older adults aged over 60. Thirty-two older adults were submitted to 6-months of MT program (EG), and 28 older adults were no treated and used as Control Group (CG). Global cognitive functioning (MMSE score), verbal and visual memory, and attention were assessed at baseline (T0) and after 6-months (T1). At the same time, plasmatic level of Cortisol (C), IL-1, IL-18, IL-6, and the expression of WIP-1 mRNA and protein in ex vivo Peripheral Blood Mononuclear Cells (PBMCs) were analyzed in young adults at T0, as well in older adults at T0 and T1. Together, the results suggest that MT improves the global cognitive functionality, verbal and visual memory, as well as the level of attention. At the same time we observed a decrease of the plasmatic level of C, of the cytokines, and an increase of the expression of mRNA and protein of WIP-1. The analysis of correlations highlighted that the level of the mRNA of WIP-1 was positively associated to the MMSE score, and negatively to the C and cytokine levels. In conclusion, we purpose the MT as tool that could help support successful aging through the improving of memory, attention and global cognitive function performance. Furthermore, this approach could participate to maintain lower the peripheral levels of the C and pro-inflammatory cytokines. The WIP-1 as a potential new target of the pathophysiology of aging is theorized.